Epidemiology of SCLC in the United States From 2000 to 2019: A Study Utilizing the Surveillance, Epidemiology, and End Results Registry - Leah E. Wells, MD; Sean Cohen, MD; Benjamin Brennan, MS; Mousumi Banerjee, PhD; Gregory P. Kalemkerian, MD (JTO Clinical and Research Reports)
Introduction: From the late 1980s to 2000, SCLC represented a decreasing proportion of lung cancer cases in the United States. Nevertheless, survival outcomes in SCLC did not improve, reflecting the paucity of treatment advances. We sought to determine whether these trends continued into more recent decades, before the Food and Drug Administration approval of immunotherapy for SCLC in 2019, by evaluating the incidence and survival of SCLC from 2000 to 2019 in the United States population, with attention to variance across gender and racial subgroups. Methods: Using the United States Surveillance, Epidemiology, and End Results 17 database, we evaluated the incidence of SCLC and NSCLC from 2000 to 2019. Demographic, staging, and survival data were collected for patients with SCLC by comparing the incidence and outcomes across groups. Results: The percentage of SCLC among all newly diagnosed lung cancer cases decreased from 14.5% in 2000 to 11.8% in 2019. A decrease in SCLC incidence was observed in all sex and racial subgroups but was earlier and steeper in men than in women. This has resulted in a shift in the male-to-female ratio from 1.14:1 in 2000 to 0.93:1 in 2019. Among the racial subgroups, the incidence of SCLC declined most slowly in non-Hispanic Whites and most rapidly in non-Hispanic Asians and Pacific Islanders. There was a decline in limited-stage SCLC at diagnosis, from 31.1% in 2000 to 26.4% in 2019. Minimal improvement was observed in survival regardless of patient characteristics or stage. Conclusions: In the preimmunotherapy era of 2000 to 2019, the incidence of SCLC continued to decline in both sexes and all racial subgroups. The male-to-female ratio continued to narrow with women outnumbering men in the most recent years. The proportion of patients with limited-stage disease continues to decline, likely because of improved staging procedures. The outcomes improved slightly but remained poor, highlighting the need for more effective treatment strategies.